Advances in 3D Bioprinting for Neural Tissue Engineering. Issue 4 (8th March 2018) - Lee, Se‐Jun; Esworthy, Timothy; Stake, Seth; Miao, Shida; Zuo, Yi Y.; Harris, Brent T.; Zhang, Lijie Grace
Abstract: Current therapies for nerve regeneration within injured tissues have had limited success due to complicated neural anatomy and inhibitory barriers in situ. Recent advancements in 3D bioprinting technologies have enabled researchers to develop novel 3D scaffolds with complex architectures in an effort to mitigate the challenges that beset reliable and defined neural tissue regeneration. Among several possible neuroregenerative treatment approaches that are being explored today, 3D bioprinted scaffolds have the unique advantage of being highly modifiable, which promotes greater resemblance to the native biological architecture of in vivo systems. This high architectural similarity between printed constructs and in vivo structures is thought to facilitate a greater capacity for repair of damaged nerve tissues. In this review, advances of several 3D bioprinting methods are introduced, including laser bioprinting, inkjet bioprinting, and extrusion‐based printing. In addition, the emergence of 4D printing is discussed, which adds a dimension of transformation over time to traditional 3D printing. Finally, an overview of emerging trends in advanced bioprinting materials is provided and their therapeutic potential for application in neural tissue regeneration is evaluated in both the central nervous system and the peripheral nervous system. Abstract : Among several possible neuroregenerative treatment approaches that are being explored today, 3D bioprinted scaffolds have the unique advantage of being highly modifiable, which promotes greater resemblance to the native biological architecture of in vivo systems. In this review, advances of several 3D bioprinting methods and bioprinting materials are discussed for their application in neural tissue regeneration.